Patterns of failure in cases of carcinoma of esophagus treated with radical concurrent chemoradiation - T, Naveen; Khaleel, Ibrahim; Kashyap, Lalit; Goyal, Surekha; HB, Govardhan; P Sridhar, Siddanna; KPR, Pramod; Sarkar, Nivedita; A., Sathish (International Journal of Medical Research and Review, 2016)
Background: Radical chemoradiation has been the main stay of treatment in inoperable cases of carcinoma of thoracic oesophagus. The purpose of the study is to determine the pattern of recurrence after radical concurrent chemoradiation. Materials and Methods: Fifty patients with carcinoma esophagus treated with chemoradiation were taken retrospectively for this study. All the patients were treated with external beam radiation therapy (3DCRT/IMRT) of 54 to 59.4Gy with 3 weekly cisplatin 80 mg/m2 and capicitabine 1250 mg /m2. All patients were followed with upper GI endoscopy at 3-4 monthly for first 3 years, CECT thorax and abdomen at every 3 month for 1 year then 6 monthly up to 3 year thereafter yearly follow up. Appropriate statistics were used for the analysis. All the patient information was taken out from the case files and by telephonic interview. Results: 50 patients were included in the retrospective analysis. Median age was 54 years. 26 (52%) were males and 24(48%) were females. Most common tumour histology being squamous cell carcinoma and most common site being the middle 1/3 of esophagus 30/50(60%). 47/50 (94%) patients received concurrent chemoradiation with cisplatin with capecitabine and 3/50 (6%) received induction chemotherapy with cisplatin and 5-FU. Patients were followed up for a period of 8 months to 34 months (median: 21 months). At the time of last follow up in September 2015, 23/50(46%) patients had local recurrence, 14 (28%) patients had distant failure and 13(26%) patients had no evidence of disease at the time of last follow up. With a median follow up of 21 months, mean overall survival for all the patients was 17.5 months. Patients surviving at the end of 1 year were 68%, at 2 years was 36%, and at 3 years was 4.3%. Conclusion: This study concludes that highest incidence of failure and recurrences occur most commonly locally (within the previously irradiated field) even after definitive radical treatment with concurrent chemoradiation. As the local recurrence is more than distant failure we should aim at consolidating the local therapy by dose escalation or alternative radiation therapy.